2022
DOI: 10.7554/elife.81196
|View full text |Cite
|
Sign up to set email alerts
|

Mobilome-driven segregation of the resistome in biological wastewater treatment

Abstract: Biological wastewater treatment plants (BWWTP) are considered to be hotspots for the evolution and subsequent spread of antimicrobial resistance (AMR). Mobile genetic elements (MGEs) promote the mobilization and dissemination of antimicrobial resistance genes (ARGs) and are thereby critical mediators of AMR within the BWWTP microbial community. At present, it is unclear whether specific AMR categories are differentially disseminated via bacteriophages (phages) or plasmids. To understand the segregation of AMR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Furthermore, sewage from both the hospital and the general population is ultimately transported to wastewater treatment plants that therefore provide a vast reservoir for AMR [44] . Importantly, the transmission of ARGs via MGEs was further highlighted recently by de Nies et al who reported the segregation of ARG categories between plasmids and phages in wastewater treatment plants [45] . Recent evidence suggests that anthropogenic forcing of environments has led to increased AMR in the environment, such as Antarctica, that was previously recognized as pristine [46] .…”
Section: Microbial Reservoirs Of Antimicrobial Resistancementioning
confidence: 80%
“…Furthermore, sewage from both the hospital and the general population is ultimately transported to wastewater treatment plants that therefore provide a vast reservoir for AMR [44] . Importantly, the transmission of ARGs via MGEs was further highlighted recently by de Nies et al who reported the segregation of ARG categories between plasmids and phages in wastewater treatment plants [45] . Recent evidence suggests that anthropogenic forcing of environments has led to increased AMR in the environment, such as Antarctica, that was previously recognized as pristine [46] .…”
Section: Microbial Reservoirs Of Antimicrobial Resistancementioning
confidence: 80%
“…Thus, while the presence of floR (a phenicol exporter) and estT (a macrolide esterase) can be rationalized by the use of both classes of antibiotics during the study period, the current global status of the mobile resistome should not be ignored. ARGs are found throughout the biosphere with water systems, in particular, biological wastewater treatment facilities impacting their patterns of dissemination in mobile genetic elements of bacteria ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…6A ), suggesting that these ARGs were transmitted through VGT (inheritance from parent to offspring). A study identified a mobile resistome in WW, where most of the ARGs were associated with chromosomes ( 35 ), and only small proportions (10.8%) were found on plasmids, highlighting the involvement of other genetic elements in the spread of ARGs. Shi et al revealed the potential of VGT through the proliferation of ARG hosts and showed that more ARGs are located on chromosomes than on plasmids ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAGs may help identify MGEs in hosts, such as plasmids. Identification of plasmids in a given host can be challenging because plasmids are self-replicating ( 35 ) and can be hosted by more than one species ( 34 , 36 ). Notably, plasmids are known to be significant vectors for gene transfer in many bacterial populations than any other mobile genetic elements ( 34 , 37 ).…”
Section: Introductionmentioning
confidence: 99%